Counting sheep - Kelly, Jacqueline (Kelly, Jacqueline. Calpurnia Tate, girl vet., 2017)
In rural Texas in 1901, thirteen-year-old Callie nurses a butterfly with a broken wing and delivers a baby lamb, despite her mother's disapproval of Callie's "unladylike behavior."